2023
DOI: 10.3390/sports11020035
|View full text |Cite
|
Sign up to set email alerts
|

Notational Analysis and Physiological and Metabolic Responses of Male Junior Badminton Match Play

Abstract: We examined the game characteristics of badminton and the physiological and metabolic responses in highly trained male junior players. Players from a Badminton England accredited Performance Centre (n = 10, age: 14.0 ± 1.2 y, height: 1.69 ± 0.06 m, body mass: 59.1 ± 5.0 kg) completed a 20-m shuttle run test (V˙O2max: 64 ± 7 mL·kg−1·min−1) and a simulated ability-matched competitive singles badminton game consisting of two 12-min games with a 2-min break wearing the COSMED K5 metabolic system with notational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Therefore, it would be difficult to find time for all‐out tests developed in previous studies (Abián‐Vicén et al., 2021 ; Chin et al., 1995 ; Madsen et al., 2016 ). This study showed that BLa increased to 3.0–4.6 mM in ranked players at stage 2 (similar tempo with Singles match) of the badminton‐specific endurance test, which is similar to BLa in badminton matches (Faude et al., 2007 ; Fernandez‐Fernandez et al., 2013 ; Green et al., 2023 ). Therefore, badminton players do not need to perform an all‐out test and need less than 10 min to determine their badminton‐specific endurance by performing only stage 2 of our protocol.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Therefore, it would be difficult to find time for all‐out tests developed in previous studies (Abián‐Vicén et al., 2021 ; Chin et al., 1995 ; Madsen et al., 2016 ). This study showed that BLa increased to 3.0–4.6 mM in ranked players at stage 2 (similar tempo with Singles match) of the badminton‐specific endurance test, which is similar to BLa in badminton matches (Faude et al., 2007 ; Fernandez‐Fernandez et al., 2013 ; Green et al., 2023 ). Therefore, badminton players do not need to perform an all‐out test and need less than 10 min to determine their badminton‐specific endurance by performing only stage 2 of our protocol.…”
Section: Discussionsupporting
confidence: 65%
“…However, badminton players appear to rest for less than double the rally time when playing longer rallies (e.g., 20 s; unpublished observation), meaning that the work:rest ratio of the badminton‐specific endurance test in this study could be similar to that of badminton games. Indeed, BLa was 3.0–4.6 mM in ranked players at stage 2 (similar tempo with Singles match) of the badminton‐specific endurance test, while that was 1.9–4.3 mM in badminton games (Faude et al., 2007 ; Fernandez‐Fernandez et al., 2013 ; Green et al., 2023 ). Therefore, our test seems to reflect endurance in badminton games well, even though it is slightly different in the work:rest ratio and lack of hitting action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Badminton is a sport that must think very quickly during the game and make the necessary movements techniques that are important to be able to hit the shuttelcock to the target or targets and badminton is a game that requires agility and balance in reaching the shuttelcock (Green et al, 2023;Marpaung & Manihuruk, 2022). The movement in badminton is to reach the shuttlecock by stepping as fast as possible while continuing to maintain good balance and keep the body under control (Sepdanius et al, 2018).…”
Section: Introductionmentioning
confidence: 99%